Moral and legal education of high school students - MAKAROV, Alexey (Journal of Education, Technology and Computer Science, 2014)
The article discusses the nature and significance of moral and legal education of high school students as a basic psychological and educational problem. The author analyses scientific positions of educational classics and makes an attempt to distinguish benchmarks helping to improve the moral and legal culture of high school students.